Morocco : 2013 Article IV Consultation-Staff Report; Press Release; and Statement by the Executive Director for Morocco. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses Morocco's 2013 Article IV Consultation on economic developments and policies. The IMF report highlights that despite unfavorable external and domestic environment Morocco's economic performance has improved during 2013. The Morocco's economy remains vulnerable to international conditions and a difficult regional environment. It focuses on the importance of giving more flexibility in the exchange rate regime that intends to support competitiveness, enhance the capacity of the economy to absorb shocks, and support the authorities' strategy for diversifying external flows away from Europe.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet